Experimental study on frame-supported multi-ribbed composite walls under low-reversed cyclic loading. Issue 3 (15th March 2016) - Suizi, Jia; Wanlin, Cao; Quan, Yuan; Yuchen, Zhang
Abstract : The paper intends to study the seismic performance of the frame-supported multi-ribbed composite wall (FSMRC wall) with large space at the bottom and with that purpose, it conducts low-reversed cyclic loading experiment to two such specimens, with their scales reduced by 1/2 of the prototypes. Afterwards, the paper looks into the major parameters – failure process, the hysteresis of the vertex-horizontal displacement and of inter-storey displacement, the skeleton curves and the loading–strain curves of the members' reinforcing steels – of the specimens, both with and without holes, and then carries out comparative studies on the results. On this basis, the stiffness degradation and the residual deformation ratio are discussed, and the experiment results stand as the following: the structure as a whole delivers an extraordinary seismic performance, thanks to the unique layer-by-layer embedded upper design. It should be noted that the failure process and the stiffness degradation of both specimens, with and without the holes, are found to be roughly consistent; at the same time, both has proven to be fairly good in terms of displacement ductility, collapse resistance and repairability.